DEVELOPMENT OF A DATA MANAGEMENT SYSTEM FOR STUDENTS’ FINAL YEAR PROJECTS CASE STUDY: DEPARTMENT OF INFORMATION SYSTEMS - Astrid Callista; Fiona Fiona (Jurusan Teknik Informatika, 2010)
With the advances of information technology nowadays, it is more than appropriate for an educational institution to make use of the existing technology to ease the process of managing students’ data and grades. One of the applications needed by the Information Systems department is a data management system for student’s final year projects that can manage their grades and generate full reports. This system will be developed as a web-based system, with access limited only to the university's local network. To design this new system, analyses of the current final year project procedure, data and grade management will be conducted. The results of the analyses will form the foundation of the design and development of a database management system – the core support of the data management system. The interface of the system will be designed and built on the principles of usability. It is aimed that both the department's administration and the Head of Department can benefit from using this system to input, manage and view students' final year projects and the respective grades.